The Crime of Rape and Sexual Violence against Women in Nigeria: A Comparison with Other Common Law Countries - Ngozi Alili (Rechtsidee, 2016)
This discourse is a comprehensive look at the offence of “rape” as a legal concept, taking into consideration, the premodial, mythical and legal beliefs and meanings associated therewith. It analysed recent statutory changes and developments in this area of the law, particularly under the English common law in contradistinction from the almost static provisions of some African penal statutes relating to the offence of rape. The propelling aim was to appreciate the difficulties associated with efforts to convict persons accused of committing the offence of rape and the legality of calling in aid corroboration in amelioration of these difficulties. It was observed that, the statutory ingredients of the offence do not accommodate such a practice. It became significant that the myths and traditional beliefs surrounding the claim of an alleged victim of rape imported the burden of a rebuttal on the accused. It was observed that sympathy on the part of the courts for alleged rape victims sway their decisions in favour of such victims. This emotional consideration by the courts may have informed he demand for corroborative evidence to seal all escape routes for the accused even when not statutorily provided for. Absence of corroborative evidence may on the reverse, favour the accused though the prosecutrix may concoct one to secure conviction. It was concluded that rape cases should be determined on the basis of the dry provisions of the relevant penal statutes devoid of extraneous considerations, such as corroboration.